Engineering Polymer Hydrogel Nanoparticles for Lymph Node‐Targeted Delivery. Issue 4 (15th December 2015) - De Koker, Stefaan; Cui, Jiwei; Vanparijs, Nane; Albertazzi, Lorenzo; Grooten, Johan; Caruso, Frank; De Geest, Bruno G.
Abstract: The induction of antigen‐specific adaptive immunity exclusively occurs in lymphoid organs. As a consequence, the efficacy by which vaccines reach these tissues strongly affects the efficacy of the vaccine. Here, we report the design of polymer hydrogel nanoparticles that efficiently target multiple immune cell subsets in the draining lymph nodes. Nanoparticles are fabricated by infiltrating mesoporous silica particles (ca. 200 nm) with poly(methacrylic acid) followed by disulfide‐based crosslinking and template removal. PEGylation of these nanoparticles does not affect their cellular association in vitro, but dramatically improves their lymphatic drainage in vivo. The functional relevance of these observations is further illustrated by the increased priming of antigen‐specific T cells. Our findings highlight the potential of engineered hydrogel nanoparticles for the lymphatic delivery of antigens and immune‐modulating compounds. Abstract : Lymphatic transportation : PEGylation is shown to be a key parameter for lymphatic transportation of hydrogel nanoparticles. The PEGylated nanoparticles result in a high association with dendritic cells and B cells as well as increased T cell responses in vivo, which can be potentially used to improve the delivery of vaccines and drugs to the lymph nodes.